2022
DOI: 10.3390/membranes12121266
|View full text |Cite
|
Sign up to set email alerts
|

Design and Utilization of a Direct Methanol Fuel Cell

Abstract: This study introduces a step-by-step, summarized overview of direct methanol fuel cell (DMFC) fundamentals, thermodynamic–electrochemical principles, and system evaluation factors. In addition, a parametric investigation of a JENNY 600S DMFC is conducted to simulate cell performance behavior under varying operating conditions. The system is mathematically modeled and solved in MATLAB and accounts for multi-irreversibilities such as the activation and ohmic and concentration overpotentials. The performance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…Meanwhile, hydrogen peroxide (H 2 O 2 ) is produced (eq 5) in a two-electron pathway and may be further reduced to yield H 2 O (eq 6). The twoelectron pathway is unfavorable in both alkaline and acidic media because intermediate (HO 2 − or H 2 O 2 ) production increases the overpotential, resulting in a lower onset potential. 49 It has been reported that the presence of intermediates affected the overpotential values.…”
Section: Mechanism Of Orr In Different Ph Electrolytesmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, hydrogen peroxide (H 2 O 2 ) is produced (eq 5) in a two-electron pathway and may be further reduced to yield H 2 O (eq 6). The twoelectron pathway is unfavorable in both alkaline and acidic media because intermediate (HO 2 − or H 2 O 2 ) production increases the overpotential, resulting in a lower onset potential. 49 It has been reported that the presence of intermediates affected the overpotential values.…”
Section: Mechanism Of Orr In Different Ph Electrolytesmentioning
confidence: 99%
“…As shown in Figure , ORR in electrochemical devices may require diverse pH conditions. Proton exchange membrane fuel cells (PEMFC) and direct methanol fuel cells (DMFC) are operated in acidic media (pH ∼ 1). , Microbial fuel cells (MFC), producing electricity through an enzymatic process of bacteria, work in a neutral pH environment (pH ∼ 7) . Meanwhile, zinc–air batteries (ZAB) and alkaline membrane fuel cells (AMFC) are suitable to work in alkaline media (pH ∼ 13). , However, the high cost and limited abundancy of Pt have hindered their commercialization. Hence, it is crucial to find alternatives for pH-universal Pt-based catalysts to promote cheap and large-scale production of ORR catalysts that can function in PEMFC, MFC, AMFC, ZAB, and other electrochemical devices, simultaneously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dehydrogenation reactions required to get hydrogen from chemical hydrogen carriers commonly employ catalysts such as Fe, Ni, Pt, and Ru to promote exothermic reactions. Therefore, the development of catalysts enabling higher hydrogen production rates and efficiency at lower temperatures, along with high-purity hydrogen extraction, is imperative [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96]. The hydrogen produced requires refinement, with coupling to existing commercial hydrogen production methods such as Steam Methane Reforming (SMR) with separation and purification facilities allowing for cost savings in hydrogen production by separating carbon monoxide and carbon dioxide [97][98][99][100][101][102][103][104][105][106][107][108][109][110][111].…”
Section: Introductionmentioning
confidence: 99%
“…Common RWGS catalysts can be Cu-based and noble metals supported on metal oxides, 9,10 Methanol is one of ubiquitous chemicals that is widely used for chemical productions and fuels. 12,13 One of possible routes to produce CH 3 OH from CO 2 is the hydrogenation of CO 2 (eq. 2).…”
Section: Co 2 Transformation and Utilizationmentioning
confidence: 99%